Is it ethical? / Raziah Bi Mohamed Sadique - Mohamed Sadique, Raziah Bi (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The ethics of tax avoidance are a subject of debate and can vary depending on individual perspectives, societal norms, and legal systems. Some argue that tax avoidance is ethically acceptable because it involves legal methods to minimize tax liability within the boundaries of tax laws and regulations. Others contend that aggressive tax avoidance can be unethical, particularly when taking advantage of loopholes or unfairly shifting tax burdens onto others. Tax avoidance is the legal practice of minimizing tax liability within the framework of tax laws and regulations. It involves using various strategies, deductions, credits, and exemptions provided by tax laws to reduce the tax burden. Tax avoidance is a legal and legitimate approach to managing one's tax liability. Tax laws are designed to allow individuals and businesses to take advantage of legitimate tax-saving opportunities. Tax avoidance strategies can include claiming legitimate deductions (e.g., mortgage interest deduction) and structuring business operations to reduce taxable income. On the other hand, tax evasion is the illegal act of deliberately misrepresenting or concealing financial information to reduce tax liability. Tax evasion is illegal and considered a criminal offense in most jurisdictions. Tax evasion practices include not reporting income earned from cash transactions, creating fake invoices to inflate expenses, using offshore accounts to hide income, and engaging in complex financial schemes to evade taxes to the extreme extent of engaging in fraudulent activities to avoid paying taxes. It involves deliberate actions to evade taxes owed, which can lead to severe penalties, including fines, imprisonment, and asset forfeiture.